The effect of adding carrot, turmeric, and pumpkin solution to Nemo (Amphiprion percula) to increase color brightness - Umar, Putra Arif Yanto; Abdullah, M. Dzaky; Mobonggi, Ghina Luthfiyyah; Patma, Patma (Science, Technology, and Education Care, 2025)
Nemo (Amphiprion percula) are interesting ornamental fish living in anemones' tentacles. The body color of Nemo fish determines Nemo's selling price and the level of consumer demand. However, the fading of color in Nemo often occurs due to internal and external factors that can cause public interest and selling value to decrease. Therefore, it is necessary to research the addition of carrot, turmeric, and pumpkin solutions to Nemo to improve their color. This study aims to increase the brightness of the color in Nemo. The research method was carried out using an experimental method using a Completely Randomized Design (CRD) of four treatments and four replications so that 16 experiments were obtained. The study's results stated that adding Carrot, Turmeric, and Pumpkin solutions to Nemo fish did not affect increasing the brightness of the color in Nemo because the F Count obtained <from F Table 5% and 1%. This study emphasizes the importance of taking longer to soak active ingredient solutions such as carrot, turmeric, and pumpkin to obtain maximum results